Plant virology in subSaharan Africa: proceedings of a conference organized by IITA, 48 June 2001 - Hughes, J.A.; Odu, B.O. (2003)
The rice yellow mottle diseases is the main virus disease found on rice in Africa. It has been reported in all major rice producing zone of sub-saharan Africa (East,West,Central and Southern Africa and Madagascar). The disease incidence and accompanying yield losses could be high depending on the rice cultivars grown, the date of infection and type of rice.